Micro structure of foreign exchange risks in commercial banks in the Caribbean - Seerattan, Dave ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Explores the impact that the micro structure of the foreign exchange markets has on the efficiency and stability of these markets in select Caribbean countries.